Viewing Another Act as You Would Creates Altruistic Desires Towards that Other - Bogdan, Paul (Frontiers in Human Neuroscience, 2017)
There has been growing evidence for the existence of distributed, frequently updating social “indices,” which are related to the reputation of others and predict altruism towards them. However, the means by which the brain modifies an index based on experiences is still unknown. This work utilizes recent insights on the role of the anterior cingulate cortex during perspective taking, dorsolateral prefrontal representations of context, the temporoparietal junction’s relationship with understanding another’s background and dorsomedial prefrontal activation patterns tracking reputation. It aims to show that cognitive empathy causes comparisons between a target’s action and the action one would wish to do in the target’s position. It also suggests that viewing a target perform the same action that one would in the target’s position, creates altruistic desires towards the target. By considering these comparisons as central to understanding prosocial and antisocial motivations, a variety of behavioral studies are better explained. This piece seeks to open questions and discussions on the interplay of those brain regions, suggest future approaches to relationship therapy, and establish fundamentals for multi-agent models aimed at normative sociality.